Acute effects of carbon fiber insole on three aspects of sports performance, lower extremity muscle activity, and subjective comfort - Ko, M.; Ma, T.; Xiong, S. (Sensors, 2023)
Carbon fiber insole (CFI), which is lightweight and stiff to reduce energy loss and help wearers perform better in sports, has recently been introduced. However, reports are scarce on the effects of CFI on sports performance, muscle activation, and wearing comfort. This study investigated the acute effects of CFI on sports performance, lower extremity muscle activity, and subjective comfort. Thirty young healthy males with shoe sizes between 260 and 270 mm performed various sports tasks (power generation, agility, and speed) and treadmill runs with wearable sensors under two experimental insole conditions (benchmark insole as a baseline, CFI). The results showed that, compared to the benchmark insole, CFI significantly improved sports performance in terms of power generation (~1.5%) and agility (~1%). However, it activated more of the Tibialis Anterior (~0.7%) and Gastrocnemius Medialis (~0.8%) muscles, and was perceived to be stiffer and less comfortable. These findings suggested that CFI could improve sports performance, but could cause more lower extremity muscle activation and subjective discomfort.